PROBLEMS AND CHALLENGES OF STARTUP FIRMS - A STUDY IN DHARWAD DISTRICT - Barki, Ganesh Bheemappa; Y. Nagaraju, (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Startup firms in Dharwad District, face challenges including difficulty securing financial resources and funding, finding and retaining skilled talent in a limited local pool, navigating complex government regulations and bureaucratic hurdles, building strong brand awareness and understanding market needs, and establishing supportive infrastructure. Lack of proper mentorship, insufficient innovation in deep-tech sectors, and the overall difficulty in building a supportive startup ecosystem also hinder growth. Startup industries are considered the driving force of economic growth and innovation, as they bring new products, services, and technologies to the market. However, startups also face a myriad of challenges that can threaten their survival and growth potential. These difficulties are not exclusive to startups; they also affect some established enterprises. But overcoming these obstacles is a laborious task for businesses with minimal resources. The aim of the study is to evaluate the challenges faced by startup in Dharwad District.